2019
DOI: 10.3168/jds.2018-15785
|View full text |Cite
|
Sign up to set email alerts
|

Are dietary strategies to mitigate enteric methane emission equally effective across dairy cattle, beef cattle, and sheep?

Abstract: The digestive physiology of ruminants is sufficiently different (e.g., with respect to mean retention time of digesta, digestibility of the feed offered, digestion, and fermentation characteristics) that caution is needed before extrapolating results from one type of ruminant to another. The objectives of the present study were (1) to provide an overview of some essential differences in rumen physiology between dairy cattle, beef cattle, and sheep that are related to methane (CH 4 ) emission; and (2) to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 136 publications
2
51
0
2
Order By: Relevance
“…The greater CP and lower NDF concentrations of the CON diet were expected to shift fermentation toward propionate production ( 45 ), thus reducing substrate availability for methanogenic bacterial activity and methane production. In contrast, the slightly greater DM digestibility of the MIX diet could have induced higher feed intake, thereby increasing passage rate and reduce methane production for MIX cows ( 46 ). This must have made up for the numerically lower methane yield and methane intensities from MIX cows than the CON cows.…”
Section: Discussionmentioning
confidence: 99%
“…The greater CP and lower NDF concentrations of the CON diet were expected to shift fermentation toward propionate production ( 45 ), thus reducing substrate availability for methanogenic bacterial activity and methane production. In contrast, the slightly greater DM digestibility of the MIX diet could have induced higher feed intake, thereby increasing passage rate and reduce methane production for MIX cows ( 46 ). This must have made up for the numerically lower methane yield and methane intensities from MIX cows than the CON cows.…”
Section: Discussionmentioning
confidence: 99%
“…For the Dutch dairy sector maximum reduction potentials by feeding strategies are estimated up to 37% compared to 1990, approximately 5% was already achieved in 2013 (Sebek et al, 2014). A recent literature review by Van Gastelen et al (2019b) gives an overview of 94 studies of dietary strategies to mitigate enteric CH4 in either dairy cattle, beef cattle or sheep.…”
Section: Reduction Potentialsmentioning
confidence: 99%
“…Nevertheless, the same levels of supplementation in sheep resulted in excessive ruminal fermentation that reduced fiber digestibility and intake. In the same way, van Gastelen et al [11] highlighted the caution needed before extrapolating results of CH 4 mitigation, mainly due to differences between dairy cattle, beef cattle, and sheep.…”
Section: Introductionmentioning
confidence: 97%
“…Although sheep have been used as an experimental rumen model for feed evaluation and feeding studies, the information on diets specifically designed for sheep is not as abundant as that for other ruminants (dairy and beef cattle), which may be because of the variety of conditions in which sheep are raised. However, the digestive physiology of sheep is quite different from cattle; mainly associated with differences in digesta retention times, rumen digestion, and fermentation characteristics [11][12][13], so the use of feeding strategies designed for beef or dairy cattle is not recommended for sheep nutrition. For example, Aguerre et al [13] observed in animals consuming lotus (Lotus corniculatus), that increasing supplementation with sorghum grain from 1% to 1.5% of body weight (BW) was effective in increasing feed intake and digestive use in cattle.…”
Section: Introductionmentioning
confidence: 99%